Association of Prolonged Disease Duration and TG/HDL-C Ratio in Accelerating Atherosclerosis in Patients with Takayasu's Arteritis. (August 2022) - Du, Juan; Ren, Yanlong; Liu, Jiayi; Li, Taotao; Zhang, Yaxin; Yang, Shiyu; Kang, Tieduo; Ning, Shangqiu; Chen, Liying; Guo, Xi; Liu, Wenxian; Pan, Lili
Background and aim: Takayasu's arteritis (TA) is a chronic inflammation that frequently involves the aorta and its major branches. It has been known that atherosclerosis can occur in some TA patients.Objectives: This study aimed to identify the risk factors associated with the development of atherosclerosis in TA.Methods: This retrospective study enrolled a total of 101 TA patients. All patients were divided into two groups according to the absence or presence of atherosclerosis. Baseline demographic features and clinical characteristics were compared between two groups. A logistic model was applied to determine the risk factors associated with the development of atherosclerosis.Results: Our data suggested that the disease duration of patients in the atherosclerosis group was significantly longer than that of patients in the non-atherosclerosis group [96(18.00, 180.00) versus 48.00(12.00, 111.00) months] ( P = .015). In addition, the average age of patients with atherosclerosis was significantly older compared to patients without atherosclerosis [44.00(38.00, 48.00)versus 28.50(24.00，37.00)years] ( P < .001). Logistic regression analysis showed that the risk of developing atherosclerosis increased by 9.2% per 1 year increase in the disease duration ( P = .005, OR 1.092, 95%CI: 1.027-1.162). Patients with TG/HDL-C ratio more than 0.8875 were associated with a 5.861fold increase of risk developing atherosclerosis ( P < .001, OR 5.861, 95%CI: 2.299-14.939).Conclusion: Our study indicated that prolonged disease duration and elevated TG/HDL-C ratio are associated with the development of atherosclerosis in TA patients.